2005
DOI: 10.1387/ijdb.052006jm
|View full text |Cite
|
Sign up to set email alerts
|

Role of Jun N-terminal Kinase (JNK) signaling in the wound healing and regeneration of a Drosophila melanogaster wing imaginal disc

Abstract: When a fragment of a Drosophila imaginal disc is cultured in growth permissive conditions, it either regenerates the missing structures or duplicates the pattern present in the fragment. This kind of pattern regulation is known to be epimorphic, i.e. the new pattern is generated by proliferation in a specialized tissue called the blastema. Pattern regulation is accompanied by the healing of the cut surfaces restoring the continuous epithelia. Wound healing has been considered to be the inductive signal to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 50 publications
7
92
0
1
Order By: Relevance
“…Other stocks used were: dlg-RNAi 4689 C2V (gift from B. Dickson, Dietzl et al 2007), validated for knockdown of Dlg and specificity , msn 06946 (msn-lacZ) (Mattila et al 2005); UAS-P35 (Hay et al 1994); UAS-bsk K53R (UAS-bsk DN ) (Weber et al 2000), UAS-aPKC DN (Betschinger et al 2003); UAS-aPKC CAAX-DN (Sotillos et al 2004); UASRas85D V12 (UAS-Ras ACT ) (Karim and Rubin 1998); UASRac1 N17 (UAS-Rac1 DN ) (Luo et al 1994); UAS-Rho1 RNAi #12734 [Vienna Drosophila Resource Center (VDRC), Dietzl et al 2007] and scrib 1 (D. Bilder).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other stocks used were: dlg-RNAi 4689 C2V (gift from B. Dickson, Dietzl et al 2007), validated for knockdown of Dlg and specificity , msn 06946 (msn-lacZ) (Mattila et al 2005); UAS-P35 (Hay et al 1994); UAS-bsk K53R (UAS-bsk DN ) (Weber et al 2000), UAS-aPKC DN (Betschinger et al 2003); UAS-aPKC CAAX-DN (Sotillos et al 2004); UASRas85D V12 (UAS-Ras ACT ) (Karim and Rubin 1998); UASRac1 N17 (UAS-Rac1 DN ) (Luo et al 1994); UAS-Rho1 RNAi #12734 [Vienna Drosophila Resource Center (VDRC), Dietzl et al 2007] and scrib 1 (D. Bilder).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the involvement of JNK signaling in the cooperation of ey.Ras ACT with RhoGEF2 and Rac1, we first tested whether JNK activity was increased in these eye discs, using the msn-lacZ reporter to monitor JNK pathway activity (Mattila et al 2005). Expression of Ras ACT via ey-GAL4 resulted in a weak induction of msn-lacZ in some cells in the eye disc ( Figure 3, A and B), which was expected because of previous findings on the regulation of Jun and Fos activity via the Ras-MAPK signaling pathway (Kockel et al 1997;Ciapponi et al 2001).…”
Section: Uas-pbl-gfp#8mentioning
confidence: 99%
“…Recently, Wagner and co-workers provided evidence that neoblasts, which are adult pluripotent stem cells, underlie the remarkable regenerative abilities of planarians (Wagner et al, 2011 Table 1 in Stocum and Zupanc, 2008). Although different, all these processes share signaling pathways and molecular mechanisms to restore normal function of the affected tissue (Bosch et al, 2005;Mattila et al, 2005;Gurtner et al, 2008). Determining how common signaling pathways are used in different processes is one of the main questions in developmental biology and regenerative medicine.…”
Section: Regeneration: Blastema Formation and The Role Of Adult Stem mentioning
confidence: 99%
“…It appears that the JNK pathway is activated in a gradient emanating from the wound limited by the scab and diffuses to the syncytium to promote cell spreading and reepithelialization. It has also been shown that the JNK pathway and its upstream regulators, the Rho family of small GTPases, are involved in localization of Nonmuscle Myo II to larval wounds (Rä met et al, 2002;Jacinto et al, 2002;Galko and Krasnow, 2004;Mattila et al, 2005;Baek et al, 2010;Kwon et al, 2010). The JNK pathway and Fos activate the expression of MMP-1, which degrades matricellular proteins during wound healing, as well as during disc eversion/regeneration and tumor invasion in Drosophila (Uhlirova and Bohmann, 2006;Srivastava et al, 2007;McClure et al, 2008).…”
Section: Wounding Drosophila Embryos Larvae and Adultsmentioning
confidence: 99%
“…22 In this period of non-responsiveness to wound signals embryonic tissues can still repair and they do so generally without producing scarring or fibrosis, suggesting the intriguing idea that scars are the result of the inflammatory process that takes place at the adults wounds. 25 Beyond their roles in the embryo, Drosophila hemocytes play an important role in efficiently fighting infections 26 and repairing tissue damage [27][28][29] during the larval and adult stages of the fly. Just before hatching into larva, the heart (dorsal vessel) begins to beat, and the hemolymph (fly blood) circulation is established.…”
Section: Hemocytes and Tumorigenesismentioning
confidence: 99%